Effects of Socio-Environmental Performance and Costs, Firm Size, and Sustainability Reporting on Financial Performance: A Mediating Analysis - Eva Wany (Universitas Pendidikan Ganesha, 2024)
There are still inconsistent findings and an unclear mediating role for Sustainability Reporting (SR) in the relationships among Socio-Environmental Performance, Socio-Environmental Costs, firm size, and financial performance. This study examines the impact of Socio-Environmental Performance, Socio-Environmental Costs, and firm size on financial performance, considering SR as a mediating variable. Using secondary data and a quantitative descriptive approach, the research sampled 21 manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2021. These companies met criteria such as consistent financial reporting, absence of consecutive losses, and participation in the Ministry of Environment and Forestry’s PROPER program. Data were collected from financial and annual reports available on the IDX and company websites. Analysis using Smart PLS 4.0 revealed that Socio-Environmental Performance and SR significantly influence financial performance, while company size does not. Additionally, Socio-Environmental Performance and company size positively influence SR, but Socio-Environmental Costs do not. SR mediates the relationship between Socio-Environmental Performance and financial performance, but not between Socio-Environmental Costs and financial performance.